2019
DOI: 10.1021/acs.jafc.9b01455
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Analysis of Available Boron Isotopes in Soil Using Multicollector Inductively Coupled Plasma Mass Spectrometry

Abstract: As a result of the important roles of boron (B) in the growth of plants, the uptake of B by plants is dependent upon the existing form and content of available B in soil, which can bring about the local cycle of B isotope equilibrium. A method using water-heating extraction combined with three-step ion-exchange chromatography was developed for the extraction and isotopic analysis of available B in soil. The extraction efficiency and fractionation of B isotopic composition in the procedure were investigated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 43 publications
(93 reference statements)
0
8
0
1
Order By: Relevance
“…Abreu et al [138] summarized their research with findings of other authors [139,140] and proposed the following scale: 0.0-0.2 ppm as low, 0.21-0.6 ppm medium, 0.61-1.1 ppm high, 1.2-3.0 ppm very high, and >3.0 ppm as toxic soil boron concentrations. It was suggested [141] that 0.5-2.0 ppm represents the optimal soil boron range, whereas lower and higher values indicate deficiency and toxicity. Disorders in boron nutrition are, therefore, quite common.…”
Section: Soil Boronmentioning
confidence: 99%
See 1 more Smart Citation
“…Abreu et al [138] summarized their research with findings of other authors [139,140] and proposed the following scale: 0.0-0.2 ppm as low, 0.21-0.6 ppm medium, 0.61-1.1 ppm high, 1.2-3.0 ppm very high, and >3.0 ppm as toxic soil boron concentrations. It was suggested [141] that 0.5-2.0 ppm represents the optimal soil boron range, whereas lower and higher values indicate deficiency and toxicity. Disorders in boron nutrition are, therefore, quite common.…”
Section: Soil Boronmentioning
confidence: 99%
“…The quantity of the extracted boron is further determined using spectrophotometric and plasma-source spectrometric methods. The validation of newly developed promising soil tests [141,163] in a wide range of soils, environmental conditions, and crops should contribute to a better understanding of complicated plant-soil interactions concerning boron uptake, translocation, and utilization.…”
Section: Soil Boronmentioning
confidence: 99%
“…(1985), management of crop B nutrition is a demanding practice as the range between deficiency and excess is narrow for B. It was suggested that 0.5–2.0 mg kg –1 represents the optimal hot water extractable soil B range, whereas lower and higher values indicate deficiency and toxicity for sensitive plant species (Sun et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Scanlon and Duggan (1979) planted eight species of trees and shrubs in a dewatered fly ash landfill in Tennessee and found elevated levels of B, Ni, Se, and, in some cases, As, Cd, Cu, and Zn in the foliar tissues. In a study by Singh et al (2016), accumulation of Cr, As, Cd, Hg, and Pb was found beyond the safe limit in the rice (Oryza sativa L.) grown in fly ash-implicated soil. Kumar et al (2008 ) also observed phytoextraction of Ni, Zn, and Cr by metal accumulating plant Indian mustard [Brassica juncea (L.) Czern.…”
Section: Introductionmentioning
confidence: 99%
“…B deficiency is commonly connected with coarse textured soils that are prone to leaching as a result of heavy rainfall in humid climates [7]. The kind and amount of bio-available B in the soil affects plant B absorption [8]. Water-soluble B concentrations is classified into five categories: very low (0.2 µg/g), low (0.25 -0.5 µg/g), medium (0.51 -1.0 µg/g), high (1.1 -2.0 µg/g), and very high (>2.0 µg/g) [9].…”
Section: Introductionmentioning
confidence: 99%